Solution behaviour of rubber seed oil-modified alkyd resins - Aigbodion A I; Bakare I O; Pillai C K S (Indian Journal of Natural Rubber Research, 2001)
Solution behaviour of rubber seed oil (RSO) alkyds having oil content of 40, 50 and 60 per cent was investigated. Viscosity measurements of the finished alkyds were carried out in toluene and dimethyl formamide (DMF) while those of samples withdrawn periodically during preparation of the alkyds were determined in toluene solution at 30_+5 oC. The parameterrs investigated include intrinsic viscosity [n], Huggins (KH), Kaemers (KK) and Mark-Houwink-Sakurada (MHS) constants (k, k and alpha). [n] values for the alkyds are found to be influenced by their capability to form hydrogen bonds are larger in DMF (a relatively basic solveent); while [n] value for sample II with less tendency to associate with solvent molecule is larger in toluene. Values of KH and KK show no regularity in their variation with respect to the type of alkyd and solvent. MHS relationship was found to be applicable to RSO alkyds. Correlation of [n] with degree of polymerization (DP) and average molecular weight from end group analysis (Mav) showed a linear relationship. Variation in molecular weight distribution (MWD) of the alkyds as deduced from the MHS constants, k and k is of the same order as that found from polydisperity indices obtained from GPC analysis of the alkyds.
Keywords: Alkyds; Intrinsic viscosity; Mark-Houwink-Sakurada equation; Rubber seed oil; Solution behaviour